2020
DOI: 10.2196/18481
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Internet on Medical Decisions of Chinese Adults: Longitudinal Data Analysis

Abstract: Background The internet has caused the explosive growth of medical information and has greatly improved the availability of medical knowledge. This makes the internet one of the main ways for residents to obtain medical information and knowledge before seeking medical treatment. However, little has been researched on how the internet affects medical decisions. Objective The purpose of this study was to explore the associations between internet behaviors… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…Yang et al pointed out that online medical platforms have become the “entrance” for many patients to see a doctor, which, to a certain extent, diverts the flow of patients with common diseases to high-level hospitals [ 72 ]. As the popularity of the Internet has grown, surfing and selecting health information has become a standard procedure before deciding whether or not to visit a hospital [ 73 ]. The popularity of the Internet and mobile Internet has broken the medical information barriers, and the public can obtain diagnosis and treatment measures for common diseases from the Internet at low cost and conveniently.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al pointed out that online medical platforms have become the “entrance” for many patients to see a doctor, which, to a certain extent, diverts the flow of patients with common diseases to high-level hospitals [ 72 ]. As the popularity of the Internet has grown, surfing and selecting health information has become a standard procedure before deciding whether or not to visit a hospital [ 73 ]. The popularity of the Internet and mobile Internet has broken the medical information barriers, and the public can obtain diagnosis and treatment measures for common diseases from the Internet at low cost and conveniently.…”
Section: Discussionmentioning
confidence: 99%
“…The authors reported that in 2017, among the investigated 185 tertiary hospitals, 253 secondary hospitals, and 26 primary hospitals, there were 161 (87.03%), 187 (73.91%), and nine (34.62%) hospitals have conducted telemedicine services, respectively ( 47 ). As of June 2020, the number of Internet medical users in China had reached 276 million, accounting for 29.4% of the total Internet users, and 26.4% of Internet users had purchased medicines and health equipment online ( 52 , 53 ). For example, in 2020, the revenue of the teleconsultation business carried out by Alibaba Health reached 5.93 million dollars, implying a year-on-year increase of 221.2%.…”
Section: Resultsmentioning
confidence: 99%
“…Searching the internet has become an increasingly popular channel for the public to seek health information. Thus, internet use may become an effective way to increase patients’ trust in a physician because that health information on the internet can serve as a supplement to reduce information asymmetry between patients and physicians [ 20 , 21 ]. Some researchers noted that online health communities provide a platform where patients can obtain health information and emotional support from other patients or physicians, help foster positive interactions between patients and physicians, and improve patients’ trust in their physicians [ 18 ].…”
Section: Introductionmentioning
confidence: 99%